The Development of Student Worksheets (LKPD) Based on Higher Order Thinking Skill (HOTS) with Nuance of Numeracy Literacy in Mathematics Subjects for Elementary School Class V Students - Paula Anastasha; Muammar; Siti Ruqoiyyah (Absis: Mathematics Education Journal, 2026)
This study is motivated by the low level of students’ numeracy literacy skills and the suboptimal use of instructional materials that facilitate higher-order thinking skills in elementary mathematics learning. Teacher-centered learning practices tend to limit students’ active participation and hinder their ability to solve contextual problems. This study aims to develop a Student Worksheet (LKPD) based on Higher Order Thinking Skills (HOTS) with a numeracy literacy orientation on plane geometry material that meets the criteria of validity and practicality. This research employed a Research and Development (R&D) approach using the 4-D model, which includes the stages of define, design, develop, and disseminate. The subjects of this study were fifth-grade students of SDN 3 Golong. Data were collected through expert validation sheets for content and media, as well as questionnaires on students’ and teachers’ responses. The results indicate that the developed LKPD has good feasibility, with a material expert validation score of 73% (feasible) and a media expert validation score of 91% (very feasible). Furthermore, the practicality level is categorized as practical, as indicated by small group trials (77%), large group trials (81%), and teacher responses (75%). Therefore, the HOTS-based LKPD with numeracy literacy nuance is considered valid and practical to be used as instructional material in elementary mathematics learning and contributes to improving contextual and meaningful learning quality.